Social Rejection, Family Acceptance, Economic Recession and Physical and Mental Health of Sexual Minorities - Nick Drydakis (Institute of Labor Economics (IZA), 2021)
Utilizing two panel datasets covering the periods 2013-2014 and 2018-2019, the study examines whether social rejection, family acceptance, and economic conditions bear an association with self-rated physical and mental health of sexual minorities. Social rejection bears a negative association with physical and mental health. Family acceptance shares a positive association with physical and mental health. Periods characterized by worse economic conditions (2013-2014 versus 2018-2019) correlate with a decline in sexual minorities' physical and mental health. It is found that women, trans people, people without higher education degrees, unemployed people, and relatively poor people, experience worse physical and mental health than the corresponding reference categories. The study indicates that sexual minorities who experienced societal rejections, such as unfair treatment in educational, workplace environments, and/or services (public/health) prompted deteriorated physical and mental health. Sexual minorities who experienced acceptance from their families over their sexual orientation status, experienced better physical and mental health. Moreover, during periods of increased aggregate unemployment, the physical and mental health status of sexual minorities was deteriorated. Antidiscrimination policies help reduce homophobic incidents and positively impact sexual/gender identity minorities' progression, self-esteem, income, and well-being. Public health services should ensure that policies are inclusive of the physical and mental health needs of sexual/gender identity minority groups. Addressing financial hardships for minority population groups should form part of the policymakers' agenda. This is among the first international studies to examine whether, during a period of economic recession, sexual minorities experience deteriorated physical and mental health.
Keywords: J70; I14; O52; 330; sexual orientation; health; mental health; minority stress; exclusion; family; economic recession; LGBT